2005
DOI: 10.1161/01.hyp.0000151622.47814.6f
|View full text |Cite
|
Sign up to set email alerts
|

Renal Angiotensin II Type-2 Receptors Are Upregulated and Mediate the Candesartan-Induced Natriuresis/Diuresis in Obese Zucker Rats

Abstract: Abstract-Recently, there has been a growing interest in studying the role of angiotensin II type-2 (AT 2 ) receptor in renal/cardiovascular function in pathological conditions. The present study was designed to determine the functional role of the AT 2 receptors on natriuresis/diuresis and compare the level of the tubular AT 2 receptor expression in obese and lean Zucker rats (12 weeks old). Under anesthesia, candesartan (angiotensin II type 1 [AT 1 ]-specific antagonist; 100 g/kg bolus) produced natriuresis/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
106
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(125 citation statements)
references
References 33 publications
17
106
1
1
Order By: Relevance
“…As a result, altered renal Na ϩ handling in AT 2 -null mice could be the result of AT 1 receptor upregulation and not a specific AT 2 receptor-mediated effect. Hakam and Hussain 19 showed that intravenous infusion of PD, a specific AT 2 receptor antagonist, abolished the CANDinduced natriuresis/diuresis in obese Zucker rats (a genetic model of obesity and hyperinsulinemia) to a greater degree than in lean rats. In their studies, direct stimulation of AT 2 receptors with CGP-42112A produced a more significant natriuresis/diuresis in obese compared with lean rats.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, altered renal Na ϩ handling in AT 2 -null mice could be the result of AT 1 receptor upregulation and not a specific AT 2 receptor-mediated effect. Hakam and Hussain 19 showed that intravenous infusion of PD, a specific AT 2 receptor antagonist, abolished the CANDinduced natriuresis/diuresis in obese Zucker rats (a genetic model of obesity and hyperinsulinemia) to a greater degree than in lean rats. In their studies, direct stimulation of AT 2 receptors with CGP-42112A produced a more significant natriuresis/diuresis in obese compared with lean rats.…”
Section: Discussionmentioning
confidence: 99%
“…The AT 1 receptors are ubiquitously expressed and are involved in mediating the Ang II-associated vasoconstriction, cell growth, and sodium retention. 2 The AT 2 receptors are expressed in various tissues 3,4 and are associated with vasodilatation, apoptosis, antiproliferation, and natriuresis 2,3,5 and, therefore, can be considered as functional antagonists to the AT 1 receptors.…”
mentioning
confidence: 99%
“…3 Selective activation of the AT 2 receptors by CGP42112 promotes natriuresis/diuresis to a greater degree in obese compared with lean Zucker rats. 3 The obese Zucker rat is a genetic model of insulin resistance that develops mild hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] In the adult kidney, AT 2 receptors are mainly localized in the glomerular mesangial cells 22,26,27 or the adventitia of the preglomerular arcuate and interlobular arteries. 28 AT 2 receptors are upregulated in the adult kidney in response to sodium depletion 27 or kidney damage 29 in obese Zucker rats 30 and spontaneously hypertensive rats (SHRs). 31 In other pathological conditions, such as stroke, an increased AT 2 receptor gene expression in the infarcted cortex was reported.…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%